Analisis Penyerapan Tenaga Kerja (Studi Pada UKM Kerupuk Sanjai di Kabupaten Lima Puluh Kota) - Iryani, Nelvia; Anwar, Syaiful (Politeknik Pertanian Negeri Payakumbuh, 2019)
Labor is a very important asset in economic activities, but often the number of workers exceeds the available employment capacity, so it is very necessary to analyze the factors that affect employment. This study aims to estimate the relationship between wage, capital, production value to the amount of employment in Kerupuk Sanjai Small and Medium Enterprises (SMEs) in Kabupaten Limapuluh Kota This type of research is field research and use questioner to 100 respondens . The analytical tool used is multiple linear regression analysis with OLS (Ordinary Least Square) method and data processing using SPSS VR.21 software. The results of the study show that all independent variabels has a significant effect on labor absorption in Kerupuk Sanjai SMEs in Kabupaten Limapuluh Kota. capital is the variable that has the most influence in the absorption of labor in the Kerupuk Sanjai Small and Medium Enterprises (SMEs) in Kabupaten Limapuluh Kota.